Kajian Konseptual Melatih Problem Solving Skills Melalui Model Problem Based Learning - Suyatman Suyatman; Muhammad Minan Chusni (Nusa Putra University, 2023)
Students master problem solving skills, which are demands of 21st century life, but in reality students' problem solving abilities are low. This study aims to analyze conceptually to train problem solving skills through the syntax reconstruction of the problem-based learning model. This research method uses a qualitative descriptive method, which describes problem solving skills and analyzes the syntax of the problem-based learning model. Data collection through literature: journals and books. Conceptual study of practicing Problem Solving skills through syntax reconstruction of the Problem-Based Learning Model results in modified syntax that emphasizes strengthening analysis.